Ultrasound BIRADS in women with or without mastalgia - Bonilla Sepúlveda, Oscar Alejandro (2021)
Introduction: Mastalgia occurs in 70 % of women, being the common cause for imaging studies, in many cases without indication. The incidence of breast cancer among women with mastalgia is 2.5 % with no association between the two. Objective: To determine the prevalence of BIRADS (Breast imaging reporting and data system) 4-5 among women with or without mastalgia, to describe demographic and clinical characteristics, and to determine the association between mastalgia and BIRADS ultrasound report 4-5. Methods: Cross-sectional analytical study in 323 users attended at the del Prado Clinic in Medellin (Colombia), between June and October 2018. The proportion of mastalgia and BIRADS 4-5 reports was calculated. Demographic and clinical characteristics were evaluated. Results: The prevalence of mastalgia was 21.4 %, and of BIRAD 4-5 was 6.2 %. Among those who had mastalgia, the frequency of BIRADS 4-5 was 2.9 %, with no statistical association OR 2.5 (95 % IC 0.58 to 11.3; p: 0.2). Conclusions: Suspicious ultrasound findings were not associated with mastalgia, which is a common indication for breast ultrasound; findings are often normal or benign.